Variations in water quality with the intervention of an agroecological project in Arboledas, Colombia - Castellanos González, Leónides; Capacho Mogollón, Alfonso E.; Ramón Valencia, Jarol (Luna Azul, 2026)
The quality of irrigation water is very important due to its role in soil conservation and food quality. Variations in the quality of irrigation water due to intervention by farmers with different farming systems are rare in Colombia. The objective of the study was to assess the variations in water quality with the implementation of an agroecological project in the Arboledas municipality, Department of Norte de Santander Colombia. The research was carried out on 15 farms where three agroecological (agroforestry) models were implemented: cedar as forestry, a fruit tree (lemon or avocado), and a short-cycle crop (corn or beans). The results of the initial sampling did not prevent the use of farm water to irrigate the planned polycultures in the municipality, despite presenting high variation coefficients for many variables. With the intervention of the agroecological models, significant variations were observed in some variables. In all models, concentrations of ammonium and manganese increased, and nitrates decreased. While the variations did not change the category of the irrigation water, they do serve as a warning sign to continue monitoring them.